Cordel: memória e comunicação em rede - Brasil, Alexia Carvalho (2006)
The first fair pamphlets were printed in Brazil just over one hundred years ago. Between tradition and invention a wider network was spread around the country and was called cordel . A cordel network, index of memory and collective creation has also expanded in time. Its production knew other communication technologies until the interconnected computer network. This research objective is to understand cordel as a shared memory and network communication solution. A production network which spreads throughout poets, singers, graphics men, editors, agents, readers and listeners. Roles that can be exchanged and superimposed in a material and information exchange network. Knowledge that circulates and stays through oral cultural practices and also by constant development in communication technology. These related aspects overlap and are revealed in a network of ideas. The ideas circulate in precarious materials. If the ideas stay is throughout the recurrence operated by the numerous and finest capillarity network choices in a social memory process. The investigation lines that weave the research are distinct: the line that concerns cordel and questions about its imaginary, about the way to map its production and observe its practice; the line that includes cordel but also corresponds to following and bringing up-to-date different natures of communication networks and their technological mediations. There are still other more general lines that refer to communication problems which go from the representation of knowledge to their relation to supports of memory. On the subject of cordel , among the theoretical areas and authors, we point out, Camara Cascudo, Rute Terra, Genevieve Bolleme and the oral culture studies of Paul Zumthor, Jerusa Pires Ferreira, Gilmar de Carvalho; from network theory and general system theory: Michel Serres, Pierre Rosentiehl e Jorge Vieira; from studies related to network investigation methodology, communication networks and digital culture: Barry Wellman, Wasserman and Faust, and Rogério da Costa. Cordel pamphlets cataloged along this research, give support to the thesis of a cordel network. Exchange network maps are drawn through indexes recorded on the fourth cover. An idea network hypothesis is sketched from themes, narratives and images settled in fair pamphlets. Structuring the data base is itself an experience of establishing connections more than making an excluding classification. Over this experience, we understand how ideas expressed in cordel survive technology updates and connect people